Excavation and Dialectical Unification of Traditional Chinese Medicine and Rehabilitation Technology System - Guangxu XU (康复学报)
The theory and practice of traditional Chinese medicine (TCM) and modern rehabilitation blend with each other. TCM embodies profound philosophical wisdom. The holistic concept of the unity of nature and man, the theories of Yin and Yang and five elements, and the concept of syndrome differentiation treatment provide new ideas for the development of modern medicine. The theoretical and practical methods of TCM are consistent with the overall functional goal of modern rehabilitation. Both the technical means of TCM and modern rehabilitation treatment methods have their own advantages. TCM treatment measures can enrich the rehabilitation intervention system with Chinese characteristics. Deep understanding of the theoretical system and treatment measures of TCM will enrich the connotation of rehabilitation, perfect the functional promotion means of rehabilitation, and improve the level of rehabilitation intervention. It is of great significance to explore the technology of TCM and construct the platform of TCM rehabilitation treatment.